2014
DOI: 10.1186/s40425-014-0042-0
|View full text |Cite
|
Sign up to set email alerts
|

Circulating tumor DNA analysis as a real-time method for monitoring tumor burden in melanoma patients undergoing treatment with immune checkpoint blockade

Abstract: BackgroundAssessment of therapeutic activity of drugs blocking immune checkpoints such as CTLA-4 and PD-1/PD-L1 can be challenging, as tumors may seem to enlarge or appear anew before regressing, due to intratumoral inflammation. We assessed whether circulating tumor DNA (ctDNA) levels could serve as an early indicator of true changes in tumor burden in patients undergoing treatment with these agents.FindingsTumors from 12 patients with metastatic melanoma undergoing treatment with checkpoint blocking drugs we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
140
3
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 191 publications
(153 citation statements)
references
References 33 publications
(30 reference statements)
9
140
3
1
Order By: Relevance
“…Small trials have shown that circulating tumor DNA level changes can mirror radiologic changes in tumor burden and may predict eventual response to ICI (34,35). These emerging technologies, which require only serial blood sampling and laboratory analysis, may compare favorably with PET/CT in terms of feasibility and accessibility among an increasing population of patients undergoing therapy with ICI.…”
Section: Discussionmentioning
confidence: 99%
“…Small trials have shown that circulating tumor DNA level changes can mirror radiologic changes in tumor burden and may predict eventual response to ICI (34,35). These emerging technologies, which require only serial blood sampling and laboratory analysis, may compare favorably with PET/CT in terms of feasibility and accessibility among an increasing population of patients undergoing therapy with ICI.…”
Section: Discussionmentioning
confidence: 99%
“…Detection of cell-free DNA was first described in 1987 by Stroun and collegues (8), and numerous articles were published in the past few years, indicative of a growing interest in this noninvasive diagnostic method (9)(10)(11)(12)(13)(14)(15)(16)(17)(18). Potential application scenarios include using ctDNA to supplement or substitute for tissue biopsies, especially in cases where tissue biopsies are risky or the quantity/quality of the tissue biopsied does not allow testing, and to use repeat sampling and genomic profiling to detect tumor evolution, response, and resistance (6,(19)(20)(21). Of interest, fluids such as urine can also be used to detect ctDNA (22,23).…”
Section: Introductionmentioning
confidence: 99%
“…With the advantages of noninvasive and overcome tumor-heterogeneity (42)(43)(44), the sequencing of plasma sample still needed more study. To reduce the sequencing errors confound with rare mutations, a NGS method termed Duplex sequencing was developed these years and may be useful in future plasma sequencing (45)(46)(47).…”
Section: Discussionmentioning
confidence: 99%